Effect of milking methods on cost efficiency and profits of Sapera dairy goat farming business - Rahmawati, Eri Chintya; Abdillah, Labib; Tri Prasetya, Adinda Yogi; Billhaq, Dody Houston (Politeknik Negeri Jember, 2025)
This study aims to determine the amount of milk production, milking duration, cost efficiency, and profit of Sapera dairy goat farming business with manual and automatic milking methods in the Trajumas livestock group. The materials used in this study were 7 Sapera goats that were lactating and 20 months old. This research method has 2 treatments, namely T0 = milking without a milking machine and T1 = milking with a milking machine. The variables observed were milk production, milking duration, cost efficiency, and business profit. Milk production at T0 = 1.61±0.58 and T1 = 1.62±0.61; and milking duration at T0 = 0.83±0.06* and T1 = 0.48±0.01. Cost efficiency is obtained from the use of automatic milking methods and produces potential profits with milking cost savings of Rp 1,354,230.30 per year, and an investment payback period of 385 days. The study concludes that automatic milking methods on a small or community scale is more efficient in terms of milking time and labor cost savings, but does not increase milk production and does not provide significant business benefits.